Kontribusi kontrol diri terhadap perilaku konsumtif belanja online pada siswa - Marbun, Burju Ruth Nauli; Purwaningsih, Dewi; Annisa, Farah (Universitas Indraprasta PGRI, 2024)
the increasing intensity of online shopping among individuals has recently attracted interest in research. This study aims to determine the effect of self-control on online shopping consumptive behavior among class X students at SMK PGRI 1 East Jakarta. This study was conducted using a quantitative survey approach. The population of this study was 298 class X students of SMK PGRI 1 East Jakarta. The sample was drawn purposively with the following criteria: 1) having an online shopping account, and 2) shopping online at least three to four times a month. The data collected amounted to 137 students who were then used as research samples. Data were collected through self-control questionnaires and online shopping consumptive behavior. Data were analyzed descriptively and inferentially. Hypothesis testing used a simple linear regression test with the help of SPSS. The results showed that self-control influenced online shopping consumptive behavior among students.